Improving Student Interests and Learning Outcomes Using Project Based E-Learning Models - Ariawan, Putu Agus; I Kadek Suartama (Journal of Education Technology, 2023)
The problem underlying this research is the ineffectiveness of the learning process after the Covid-19 pandemic which resulted in low interest in learning and student learning outcomes. So it is necessary to restore the learning process through appropriate learning models and by the development of the times of students and be able to overcome the learning loss during the Covid-19 pandemic. The purpose of this study was to analyze differences in interest and learning outcomes in Informatics between students who studied with the Project E-Learning learning model compared to students who studied using the direct e-learning learning model. So that this research is expected to be able to provide an overview of learning models that are more effective in informatics subjects and can increase students' interest and learning outcomes, especially in the era of the Industrial Revolution 4.0. The population of this quasi-experimental study with the posttest-only non-equivalent control group design plan was Class IX students of junior high school with two classes selected as samples using a group random sampling technique. Data were analyzed descriptively and using Multivariate Analysis of Variance/MANOVA with a significance level of 5%. The results showed that there were differences in interest and learning outcomes between students who studied with the project-based e-learning model and students who studied with the direct e-learning model, with better results for students who studied with the project-based e-learning model.